Creative social change - Goldman Schuyler, Kathryn; Baugher, John Eric; Jironet, Karin (Building leadership bridges,, 2016)
What is our role in creating healthy organizations and a healthy world? Creative Social Change fosters a unique dialogue on the interconnections between leadership, sustainability, the long-term viability of the planet, and organizational development. Brought together, these arenas of research and action can influence events globally and contribute to creating a healthy society. The book builds on interviews with five eminent social scientists, thought leaders for many decades on the nature of organizational and societal development: Robert Quinn, Otto Scharmer, Edgar Schein, Peter Senge, and Margaret Wheatley. It includes contributions on what is needed for change from longstanding creative scholar-practitioners such as Riane Eisler and Karl-Henrik Robert, as well as new voices, and concludes with a variety of concrete case studies from around the world about efforts in this direction. Embracing all levels of thinking, from the conceptual to the concrete, the book generates a foundation for scholarly research and proposes practical questions that can be used for dialogue and action among leaders, policy makers, and organizational consultants.